SHATTERED - Jessica Adriani Sutikno; Stefanny Irawan (Kata Kita: Journal of Language, Literature, and Teaching, 2017)
This creative project is a novel that is telling the story of a man named, Andri, who is jobless and desperately looking for a job. In his desperation, his uncle comes and offers him a job as a driver. He accepts the job and he meets a little girl, Helena, who is living in a wonderful house and has a good life. It turns out that Andri is a pedophile and he is trying hard to resist his temptation and desire towards Helena. In this story, I use pedophilia as my topic and my theme is that pedophilia needs to be healed. This is to help me stated my purpose in writing this work which is raising people’s concern towards pedophilia by telling them the inside story of a pedophile. During the story, because Andri could not hold his desire towards Helena, he will go to the prison to be responsible of what he did towards Helena. During his time at the prison, he kills himself because he could not hold all the negative treatments and reactions from the society and surroundings. In here, the society represents people and their negative reactions towards pedophiles. As for the genre, I choose tragedy for the genre of my story. This genre will help me in stating and creating the situation for the story.